2011 Social Accounting Matrix for Senegal - Fofana, Ismaël; Diallo, Mamadou Yaya; Sarr, Ousseynou; Diouf, Abdou (International Food Policy Research Institute, 2015)
This document describes the construction of a social accounting matrix (SAM) for Senegal. The SAM is based upon 2011 national accounts statistics and provides a consistent framework for the assessment of growth and employment policies.